The Identification of Financial Literacy Level (Accounting) of MSMEs Actors in the Wetlands Area (Study of MSMEs Actors in Pemakuan Village, Banjar Regency) - Maulana Rizky (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
This study aims to identify the accounting literacy level of MSMEs actors in the wetlands area in preparing financial statements. The Institute of Indonesia Chartered Accountants (IAI) has been provided an accounting standard to MSMEs actors in Indonesia. The financial accounting standard of Micro, Small, Medium Enterprises (MSMEs) designed by IAI aims to guide MSMEs actor in preparing financial reports and assisting in access banking. The method used in this study is descriptive qualitative. The type of data used in this study is primary data obtained through interviews with MSMEs actor in the wetlands area. Their core business is carried out in producing sago palms into wet sago in Pemakuan Village, Banjar Regency. The businessman produces sago palms into wet sago to become characteristics of the region. However, in fact, they still cannot develop better as long as limited access to banks. The results of the study stated that MSMEs actors in the wetlands area did not have knowledge in preparing financial statements. The businessman of MSMEs in Pemakuan village did not record the process of credits and debits at all. They consider that it is difficult to do bookkeeping such as recording credits and debits. Moreover, a low level of education greatly affects the assessment of the importance of recording financial activities. The SAK EMKM, which set on 1 st January 2018, will be difficult to implement by the actors of micro, small and medium enterprises that have been ratified by the Institute of Indonesia Chartered Accountants. Keywords: Micro Small Medium Enterprises (MSMEs), Wet Lands, Sago